Evaluation des Trabecular Bone Score (TBS) in der täglichen Praxis bei Patienten mit entzündlich rheumatischen und nichtentzündlichen Erkrankungen: Korrelation mit konventioneller Knochendichtemessung und Prävalenz von Wirbelkörperfrakturen - Buehring, B. (Z Rheumatol, 2020)
BACKGROUND: Osteoporosis-related fractures are common in patients with rheumatoid arthritis (RA). Bone mineral density (BMD) measurements using dual-energy x‑ray absorptiometry (DXA) alone has only a limited value for predicting the risk of fractures. The trabecular bone score (TBS) is a surrogate parameter for trabecular microarchitecture of bone and a predictor of fracture risk independent of BMD. AIM: To examine the prevalence of BMD, TBS and osteoporosis-related vertebral fractures (VF) in patients with RA in comparison to controls with non-inflammatory musculoskeletal diseases. METHODS: Data from patients with RA diagnosed by a rheumatologist and with TBS and DXA measurements, who were assessed in this hospital between 2006 and 2014 were retrospectively analyzed. The RA patients were matched with controls with non-inflammatory musculoskeletal diseases. “Reduced bone health” was defined as a T‑score <−1.0 and/or a TBS value <−1.31. Statistical analyses were carried out using the Mann-Whitney test and the Wilcoxon test. RESULTS: Data from 143 patients with RA (age 72.1 ± 11.1 years, 72% female) and 106 controls (age 69.6 ± 12.6 years, 75% female) were included. The RA patients more frequently had low BMD (n = 102, 71.3%) and low TBS values (n = 125, 87.4%) compared to controls (n = 63, 59.4% and n = 79, 74.5%, p = 0.049 and p = 0.009, respectively). The RA patients had more VF (n = 52, 36.4%) than controls (n = 24, 22.6%, p = 0.02). A total of 20 patients with VF (26.3%) had normal lumbar spine BMD and 9 (11.8%) also had a normal hip BMD. In patients with VF the combination of low TBS with normal spine BMD was more common than a normal TBS and low spine BMD (p = 0.008 for patients with RA, p = 0.025 for controls). DISCUSSION: It is known that VF can occur in patients with normal BMD. In patients with VF, a low TBS with normal spine BMD is found more frequently than normal TBS and low spine BMD. These results suggest that measurement of the TBS has the potential to be a useful tool to detect increased fracture risk in patients with RA and normal spine BMD.